Pengaruh Parameter Pemotongan CNC Milling dalam Pembuatan Pocket terhadap Getaran dan Kekasaran Permukaan pada Crankcase Mesin Pemotong Rumput - Kaisan, Idris; Rusiyanto, Rusiyanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
The purpose of the research is to find and prove the influence of machining parameters on vibration and roughness in the pocket milling process. The experimental method is used to improve the quality of products produced by CNC milling, the parameters used in the study are spindle rotation speed with variations of 300 rpm, 1200 rpm, and 3200 rpm, the depth of feed used is 2 mm and 0.5 mm. Then the test is carried out with a vibration test and surface roughness test. The data analysis technique used is descriptive statistics. The results obtained are the use of machining parameters affect the quality of the product in terms of roughness and vibration of the engine, with higher spindle rotational speed resulting in lower roughness values. The smaller the depth of feedings, the finer the roughness, then the higher the spindle rotation speed, then vibration will be lower, then the greater the depth of feed, the higher the vibration value.